Pengaruh Gaya Kepemimpinan Terhadap Kinerja Manajerial pada Pimpinan Cabang Pemuda Muhammadiyah Di Kabupaten Gresik - Alfarisi Hudan Hakiki; Rahmat Agus Santoso (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The purpose of this study is to determine the effect of leadership style on managerial performance in the leadership of the Muhammadiyah youth branch in Gresik district. This study uses a quantitative approach. Quantitative research is a research that basically uses an explanatory approach. The data collection technique used in this study is the Google form. Data analysis was carried out through a direct effect test. This test is carried out to see the value of the direct influence between variables. This test was carried out using the bootstrapping method using smartPLS 3.0 and looking at the calculation of the total direct effect. The results of this study are in the form of leadership style which has a positive and significant effect on the managerial performance of PCPM in Gresik. The more leaders in PCPM have a leadership style that suits their management, the higher the managerial performance of PCPM in districts in Gresik.